Legal protection in restitution to the victims of human trafficking - Novika, Giofanni Dian; Disemadi, Hari Sutra; Rochaeti, Nur (Faculty of Law, University of Muhammadiyah Malang, 2020)
The modus operandi offered by traffickers makes victims often deceived by these enticements. This phenomenon is caused by various social factors such as poverty. Reality like this is what makes them easily trapped in the world of slavery. The research method used in this paper is normative juridical research, using the statutory approach and the conceptual approach. Research shows an increase in cases of human trafficking is a serious problem that requires a quick reaction in handling. Legal protection for victims can be specifically protected by restitution or compensation given to the victim or family by the perpetrator.